KT2 alleviates ulcerative colitis by reducing Th17 cell differentiation through the miR-302c-5p/STAT3 axis - Gu, Dandan; Nan, Qiong; Miao, Yinglei; Yang, Hailong; Li, Maojuan; Ye, Yan; Miao, Jiarong (European journal of cell biology, 2022)
The abnormal differentiation of Th17 cells aggravates ulcerative colitis (UC). Antimicrobial peptides (AMPs) exert pivotal protection functions against UC. KT2 is a cationic AMP that mediates colon cancer development. However, KT2′s function in UC remains unclear. The UC mouse model was induced by administering 2.5% dextran sulfate sodium, and the mice were given an enema of KT2. KT2′s function in UC and Th17 cell differentiation in vivo was evaluated through various molecular experiments. The KT2′s function in Th17 cell differentiation in vitro was evaluated by the proportion of CD4+ IL-17+ T cells, IL-17 levels, and RORγt expression levels. Meanwhile, the mechanism was assessed through quantitative real-time PCR, various loss-of-function assays, and dual-luciferase reporter gene assay. KT2 restrained Th17 cell differentiation in both in vivo and in vitro UC models and slowed the UC process. KT2 elevated miR-302c-5p expression, as well as restrained Th17 cell differentiation by increasing miR-302c-5p. Meanwhile, miR-302c-5p interacted with the signal transducer and activator of transcription 3 (STAT3) and negatively regulated its expression. Furthermore, our data revealed that KT2 restrained the activation of STAT3 by elevating miR-302c-5p, thereby inhibiting Th17 cell differentiation. KT2 alleviates UC by repressing Th17 cell differentiation through the miR-302c-5p/STAT3 axis. •Antimicrobial peptide KT2 can relieve the symptoms of ulcerative colitis in mice.•Antimicrobial peptide KT2 can inhibit the differentiation of Th17 cells in vitro and in vivo.•Antimicrobial peptide KT2 can up-regulate miR-302c-5p.•MiR-302c-5p targets STAT3 and negatively regulates its expression.